The common characteristics of cotton fishing net twines—A preliminary account - Kuriyan, J K; Cecily, P J (Indian Journal of Fisheries, 2016)
The common fibres used in India as fishing net twines are Cotton (Gossipiumspp.) and Sun-Hemp {Crotalaria junced) both of which are producedin the country. Cotton is by far the most important fishing gear materialall over the world. India ranks as a premier cotton growing country beingonly second to U.S.A. in the total area cultivated. In this communicationan account of the characteristics of cotton twines, subjected to the preliminarytests, are presented.